Refining the workhorse oil market model - Zhou, Xiaoqing (Federal Reserve Bank of Dallas, Research Department, 2019)
The Kilian and Murphy (2014) structural vector autoregressive model has become the workhorse model for the analysis of oil markets. I explore various refinements and extensions of this model, including the effects of (1) correcting an error in the measure of global real economic activity, (2) explicitly incorporating narrative sign restrictions into the estimation, (3) relaxing the upper bound on the impact price elasticity of oil supply, (4) evaluating the implied posterior distribution of the structural models, and (5) extending the sample. I demonstrate that the substantive conclusions of Kilian and Murphy (2014) are largely unaffected by these changes
https://ssrn.com/abstract=3473104
Keywords: Graue Literatur; Oil market; global real activity; structural VAR; narrative sign restrictions; identification; Bayesian inference